واقع التسويق السياحي في الجنوب الجزائري - نموذج ولاية الوادي - - سليمان, غيوط (University of eloued جامعة الوادي, 2020)
"ملخص الدراسة : تهدف الدراسة إلى الكشف عن واقع التسويق السياحي في الجنوب الجزائري حيث تم أخذ ولاية الوادي كنموذج, وقد عمدت الدراسة إلى تسليط الضوء على عناصر المزيج التسويقي ومدى فاعليتها في المؤسسات السياحية بالوادي من خلال قياس مدى استجابة السائحين على السياسات التسويقية المطبقة. ولغرض تحقيق أهداف الدراسة فقد تم الاستعانة باستبيان لجمع البيانات، حيث كان مجتمع الدراسة مؤلف من زبائن المؤسسات السياحية بولاية الوادي والذين لهم علاقة واتصال مباشر مع المؤسسات السياحية، أما عن عينة الدراسة فكانت عبارة عن (80) استمارة وزعت على السائحين، والذين تم اختيارهم وفق المعاينة العشوائية ،وقد تم استخدام عدد من الأساليب الإحصائية في برنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS) لعرض وتحليل واختبار فرضيات ونتائج الدراسة، وقد توصلت الدراسة إلى أن استخدام التسويق السياحي بالوادي ضعيف ويفتقر للكفاءات في مجال التسويق السياحي إلا أن هناك مؤشرات ايجابية توحي بإمكانية تطويره مستقبلا. وفي المقابل لمسنا من قبل السائحين بالوادي دراية كافية حول التسويق السياحي ومعيقاته بالولاية.""summary of the study : The study aims to reveal the reality of tourism marketing in southern Algeria, where the wilaya of eloued was taken as a model, and the study aimed to shed light on the elements of the marketing mix and the extent of their effectiveness in the tourism establishments in the eloued by measuring the response of tourists to the applied marketing policies. For the purpose of achieving the objectives of the study, a questionnaire was used to collect data, as the study population was composed of customers of the tourism establishments in the wilayat of the eloued who have a direct relationship and contact with the tourism institutions, and as for the study sample, it consisted of (80) forms distributed to the tourists, who were selected according to Random sampling, and a number of statistical methods have been used in the Statistical Package for Social Sciences (SPSS) program to present, analyze and test the hypotheses and results of the study, and the study concluded that the use of tourism marketing in the eloued is weak and lacks competencies in the field of tourism marketing, but there are positive indicators suggesting the possibility of developing it. In the future. On the other hand, tourists in the eloued have seen enough knowledge about tourism marketing and its obstacles in the state"
مذكرة تسويق سياحي وفندقي
Keywords: التسويق السياحي, المزيج التسويقي السياحي, مؤشرات التسويق السياحي; tourism marketing, tourism marketing mix, Tourism Marketing Indicators